2017
DOI: 10.1038/srep46538
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intraventricular haemorrhage in preterm infants using time series analysis of blood pressure and respiratory signals

Abstract: Despite the decline in mortality rates of extremely preterm infants, intraventricular haemorrhage (IVH) remains common in survivors. The need for resuscitation and cardiorespiratory management, particularly within the first 24 hours of life, are important factors in the incidence and timing of IVH. Variability analyses of heart rate and blood pressure data has demonstrated potential approaches to predictive monitoring. In this study, we investigated the early identification of infants at a high risk of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Several recent publications use detrended fluctuation analysis of vital signs to predict IVH. 14,15,16 It is important to note that IVH prediction has its limitations in retrospective studies such as ours due to the fact that the exact timing of the event is unknown. Abnormal HR and SpO 2 patterns in the first 12 hours after birth can represent disturbances caused by the hemorrhage rather than a warning of the event occurring later.…”
Section: Discussionmentioning
confidence: 97%
“…Several recent publications use detrended fluctuation analysis of vital signs to predict IVH. 14,15,16 It is important to note that IVH prediction has its limitations in retrospective studies such as ours due to the fact that the exact timing of the event is unknown. Abnormal HR and SpO 2 patterns in the first 12 hours after birth can represent disturbances caused by the hemorrhage rather than a warning of the event occurring later.…”
Section: Discussionmentioning
confidence: 97%
“…In premature newborns, HRV changes can be seen preceding the development of intraventricular hemorrhage. 83,84 Whether ANS dysfunction in these newborns contributes to brain injury or whether ANS dysfunction is a more sensitive clinical early biomarker, is not exactly known.…”
Section: How Ans Failure During Transition May Lead To Brain Injurymentioning
confidence: 99%
“…The next step in this continuum of work is to develop real-time ANS monitoring which can be used at the maternal (fetal) or neonatal bedside in both research and in clinical practice settings to identify a fetus (or newborn) at risk of impaired ANS function/development. HRV analysis methods have already been studied and may predict intraventricular hemorrhage, 84 brain injury pattern, 49 developing necrotizing enterocolitis, 64 and risk for apparent life threatening events. 4 This technology therefore has the potential to reduce brain injury and adverse neurologic outcomes in high-risk pregnancies and premature or other at-risk newborns.…”
Section: Important Areas For Future Focusmentioning
confidence: 99%
“…Furthermore, several animal studies have demonstrated that excessive V T delivery during PPV in the delivery room causes brain inflammation and injury 20–23. The pathways by which PPV causes brain inflammation and brain injury include (1) altered pulmonary venous return and left ventricular output resulting in rapid abnormal fluctuations to cerebral blood flow, (2) fluctuations in blood pressure due to variable V T during PPV,24 (3) initiation of pulmonary inflammation, which initiates a systemic and subsequent cerebral inflammatory cascade and (4) a sudden rather than gradual increase in oxygen delivery causing a vascular response in the brain 22. Animal studies using premature lambs by Polglase et al 20 22 and Skiӧld et al 21 demonstrate that V T s>8 mL/kg cause brain inflammation and brain injury which is evident within 90 min after initiation of PPV.…”
Section: Introductionmentioning
confidence: 99%